You can't block me: When social media spaces are public forums. Issue 1 (2nd January 2020) - Morris, Pamela L.; Sarapin, Susan H.
ABSTRACT: Since their inception, social media spaces such as Facebook and Twitter have been legally considered private spaces that are not subject to the protections of the First Amendment. Rightly so, for (as many forget) the First Amendment applies to government actors, action, and public spaces, and the Internet is not one of those. However, in 2018, the Knight v. Trump ruling in favor of plaintiffs extended First Amendment protections via the public forum doctrine to those seeking access to (but who have been blocked from) participating in discussions on President Trump's Twitter account. Numerous other similar cases across the country have found that public officials who use social media to communicate with constituents have established a designated public forum. They therefore cannot choose who is allowed into that space and who is not by blocking (disallowing access for) some members of the public, because this constitutes viewpoint discrimination. This decision is important in bringing forum doctrine into the technological age, and it opens important spaces for democratic deliberation. This article explains the specific requirements for a social media space to be considered a public forum from Knight v. Trump, describes related cases that are using it as a precedent, and explores the implications and unresolved issues related to this case.